A laboratory-scale 3-axis automated storage and retrieval system prototype for electronic component management - Sri Kusumastuti; M. Ihya’ Ulumuddin; Cleva Tusara Kumbalany; Sihono Sihono; Vinda Setya Kartika; Raditya Artha Rochmanto; Suryono Suryono; Aminuddin Rizal (Politeknik Negeri Lhokseumawe, 2026)
Efficient storage and retrieval of electronic components remain challenging in laboratory-scale environments due to reliance on manual handling. This study presents the development and experimental evaluation of a laboratory-scale three-axis Automated Storage and Retrieval System (ASRS) prototype designed for electronic component management. The proposed system uses a combination of servo and stepper motors to provide controlled motion along the X, Y, and Z axes. It is managed by a Programmable Logic Controller (PLC) integrated with a Human–Machine Interface (HMI). Manual operation is used for system calibration and motion adjustment, while automatic operation facilitates sequential storage and retrieval processes. We evaluated the system's performance by measuring positional accuracy and deviation at multiple target rack locations. The results show that the system achieves positioning accuracy of 84.62% - 95.38%, with absolute deviations between 0.3 and 1 cm. These findings demonstrate that the ASRS prototype is a feasible solution for effective laboratory-scale automation in storage applications and for PLC-based educational purposes.